2017
DOI: 10.1371/journal.pgen.1006743
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of estrogen for the mammalian female in regulating semen coagulation and liquefaction in vivo

Abstract: Semen liquefaction changes semen from a gel-like to watery consistency and is required for sperm to gain mobility and swim to the fertilization site in the Fallopian tubes. Kallikrein-related peptidases 3 (KLK3) and other kallikrein-related peptidases from male prostate glands are responsible for semen liquefaction by cleaving gel-forming proteins (semenogelin and collagen). In a physiological context, the liquefaction process occurs within the female reproductive tract. How seminal proteins interact with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…To assess this, we generated a similar model in which ESR1 was deleted in the vaginal epithelium using the Wnt7a cre/+ ( Wnt7a cre/+ ; Esr1 f/f ) 22 . Our Wnt7a cre/+ ; Esr1 f/f females ovulate normally without the need for an exogenous gonadotropins 3 . These Wnt7a cre/+ ; Esr1 f/f females are also receptive to copulation 3 , allowing us to validate the role of ESR1 in maintaining vaginal tissue integrity after physical stress in vivo .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…To assess this, we generated a similar model in which ESR1 was deleted in the vaginal epithelium using the Wnt7a cre/+ ( Wnt7a cre/+ ; Esr1 f/f ) 22 . Our Wnt7a cre/+ ; Esr1 f/f females ovulate normally without the need for an exogenous gonadotropins 3 . These Wnt7a cre/+ ; Esr1 f/f females are also receptive to copulation 3 , allowing us to validate the role of ESR1 in maintaining vaginal tissue integrity after physical stress in vivo .…”
Section: Introductionmentioning
confidence: 84%
“…Our Wnt7a cre/+ ; Esr1 f/f females ovulate normally without the need for an exogenous gonadotropins 3 . These Wnt7a cre/+ ; Esr1 f/f females are also receptive to copulation 3 , allowing us to validate the role of ESR1 in maintaining vaginal tissue integrity after physical stress in vivo . Additionally, we used this model to investigate the role of vaginal epithelial ESR1 for both neutrophil recruitment/infiltration and maintenance of the vaginal microbiota.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The importance of estrogens in epididymal development and function has been extensively studied (Hess, Bunick, & Bahr, ; Hess, Bunick, & Bahr, ; Hess, Zhou et al, ; Joseph et al, ). Comparatively, the boar has elevated estrogens levels in blood and semen (reviewed by Hess ()), which have physiological relevance for spermatogenesis (Carreau, Bouraima‐Lelong, & Delalande, ), epididymal maturation (Hess et al, ) and postejaculatory events (Li, Garcia, Gewiss, & Winuthayanon, ). The impact of anti‐GnRH immunization on luteinizing hormone (LH) and follicle stimulating hormone (FSH) secretion impairs steroidogenesis, reducing estradiol and estrone sulfate plasma levels to 40 pg/ml (Kubale et al, ) and 0.2 ng/ml (Zamaratskaia et al, ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the uterus, the expression of Klk1 and its subfamily members are estrogen (E 2 )-dependent. Accordingly, our previous work showed that Klk1b5 is expressed at the highest level compared to other Klk members in the mouse uterus after E 2 treatment (Li, Garcia, Gewiss, & Winuthayanon, 2017). However, the physiological function of Klk1b5 has never been investigated.…”
mentioning
confidence: 98%